Anisotropic Bulk Viscous Fluid Cosmological Model with Zero-Rest-Mass Scalar Field and Time-Dependent Cosmological Term - Verma M.K.; Singh M.K.; ShriRam (My University, 2025)
In this paper, we have investigated Bianchi type-III cosmological model in the presence of a bulk viscous fluid together with zero-rest-mass scalar field and time-dependent cosmological term. We have shown that the field equations are solvable for any arbitrary cosmic scale function. Exact solutions of Einstein's field equations are obtained which represent an expanding, shearing, non-rotating and decelerating model of the universe. Some physical and geometrical behaviours of the cosmological model are discussed. © 2011 Springer Science+Business Media, LLC.